2014
DOI: 10.1155/2014/419518
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Evaluation for Antibacterial and Antifungal Activities of N-Heteroaryl Substituted Benzene Sulphonamides

Abstract: The synthesis and biological activity of N-heteroaryl substituted benzene sulphonamides (3a–h) were successful. Simple condensation reaction of benzene sulphonyl chloride (1) with substituted heteroaromatic compounds (2a–h) under dry pyridine and acetone gave the target molecules (3a–h) in good to excellent yield. The compounds were characterized using FTIR, 1HNMR, and 13CNMR. The compounds were screened for antibacterial activity against E. coli, Salmonella typhi, P. aeruginosa, B. cereus, K. pneumonia, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The absorption band at 224-200 nm corresponds to the π → π* transition of the benzene rings, and the absorptions at 290-253 nm and 341-300 nm were assigned to the π → π* of the double-bonded carbons and n → π* transitions and the azomethine group (HC=N) of 2aminopyridine respectively. The prominent band at 330 nm is associated with ligand -metal charge transfer of Cu (II) complex and the broadband at the 599 nm region corresponds to the d−d transition of the Cu(II) complexes [23,24]. The band at 334.09-375.25 nm was assigned to ligand-metal charge transfer transition (LMCT) of iron (II) complex and the broad electronic band at 612 nm region corresponds to the d-d transition of the Iron (II) complex [4,23].…”
Section: Electronic Analysis Of 4-methyl-n-(pyridin-2-yl)benzene Sulp...mentioning
confidence: 99%
“…The absorption band at 224-200 nm corresponds to the π → π* transition of the benzene rings, and the absorptions at 290-253 nm and 341-300 nm were assigned to the π → π* of the double-bonded carbons and n → π* transitions and the azomethine group (HC=N) of 2aminopyridine respectively. The prominent band at 330 nm is associated with ligand -metal charge transfer of Cu (II) complex and the broadband at the 599 nm region corresponds to the d−d transition of the Cu(II) complexes [23,24]. The band at 334.09-375.25 nm was assigned to ligand-metal charge transfer transition (LMCT) of iron (II) complex and the broad electronic band at 612 nm region corresponds to the d-d transition of the Iron (II) complex [4,23].…”
Section: Electronic Analysis Of 4-methyl-n-(pyridin-2-yl)benzene Sulp...mentioning
confidence: 99%
“…Sulfonamides are considered the synthetic antimicrobial agents acting as competitive dihydropteroate synthetase enzyme inhibitors. They are used to treat several gastrointestinal and urinary tract infections (Igwe and Okoro, 2014) [19] . Autoclaving of the incurred piglet muscle tissue results in a maximum reduction (29.6%) of sulfamethazine followed by the boiling (18%), while the microwave (15%) is the least significant (Papapanagiotou et al, 2005) [37] .…”
Section: Sulfonamidesmentioning
confidence: 99%
“…Subsequent experiments (LC/MS, 1D NMR) revealed that dihydrobenzothiadiazepine 1,1-dioxides 118 (Scheme 27) are not stable in DMSO-d 6 at room temperature, and 2D NMR spectroscopy confirmed an unprecedented ring contraction yielding 4H-benzo[b] [1,4]thiazine 1,1-dioxides 119 (Scheme 28). 76 Target compounds 120 are not cyclic benzenesulfonamides, but the rearrangement is included here to show the synthetic possibilities of the nitrobenzenesulfonamide chemistry.…”
Section: Scenario B: Combined Function Of the Nos Groupmentioning
confidence: 99%
“…Deprotection of the Nos group and subsequent acylation of 29 with acids or their halogen derivatives provided the key intermediates 30, which were subjected to different cyclization reactions leading to heterocycles 31, 32, and 33. α-Acylamino ketones were also used to prepare trisubstituted 1H-imidazoles 34. 49 Recently, trisubstituted benzo [1,4]diazepin-5-one derivatives 35 were synthesized by a similar approach (Scheme 8). 50 Unlike the previous case, the deprotected precursor 29 was first acylated with 2-nitrobenzoic acid, and further reduction of the nitro group was followed by spontaneous intramolecular on-resin cyclization.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation